Faktor-Faktor yang Mempengaruhi Penanaman Modal Asing: Studi Kasus Kota Surabaya Tahun 2019-2023 - Yuda, Yuda Shagy Rahmanda Putra; Huda, Syamsul; Perdana, Putra (Masyarakat Ekonomi Syariah Bogor, 2024)
Investment has an important role in the progress of a region's economic growth. Supported by a good investment climate, investment activities will certainly proceed according to plan. The city of Surabaya is one of the largest cities that has investment potential which can be utilized well for the progress of the city itself and country. Investment can be influenced by factors such as inflation, exchange rates, GDP and technology.This research aims to determine the effect of inflation, exchange rate and GDP on foreign investment in 2019-2023. The method used in this research is a time series with 20 observations. The results of this research are that inflation, exchange rate and GDP do not significantly influence foreign investment. Together in the long term, inflation has an influence on foreign investment. Then in the short term, inflation and GDP together influence foreign investment